The Role of Environmental Taxes as a Fiscal Instrument for Mitigation of Environmental Pollution: Lithuanian Case - Miceikiene, Astrida; Lideikyte, Jurate; Savickiene, Jurate; Cesnauske, Jevgenija (European Scientific Journal, ESJ, 2019)
Environmental taxes are an important fiscal instrument for a country, as they help in the effortstowardsthe environmental policy goals. Taxes based on the polluter-pays principle influence the behaviour of market participants by discouraging them from undertaking an environmentally detrimental activity and by attracting additional budget funds for mitigation of the consequences of this kind of activity. Environmental protection is one of the priority areas in the Republic of Lithuania, meaning that it is highly important to assess the effect of the environmental taxes on the environmental pollution in the country and improve them following the best practice of other countries. The methodology of empirical research is based on the methods of descriptive statistics. According to the official statistics of Lithuania, majority of the environmental taxes collected and the maximum volumes of the emissions into the atmosphere are generated by the following groups of economic activities: agriculture, forestry and fishing; manufacturing; wholesale and retail trade, repair of motor vehicles and motorcycles. The study of trends in the environmental tax dynamics in Lithuania and other countries has demonstrated that Lithuania is the country which moves towards an environmental tax reform. Nonetheless, it is important to reconsider the country’s environmental tax rates and tax benefits and provide for the incentives for the groups of economic activities which are characterised by the highest GDP potential and lower environmental pollution.